Effect Analysis of the Service Quality on Customer Satisfaction at PT. Bee Logistics Transworld Surabaya - Andira Puspita Fajarini (Journal of World Conference (JWC), 2019)
PT. Bee Logistics Transworld has service quality that each variable can influence customer satisfaction such as Tangible, Reliability, Responsiveness, Assurance and Empathy. This study aims to determine the effect of Service Quality on Customer Satisfaction. The population of this research is customers of PT. Bee Transworld Logistics Surabaya. Samples of 100 respondents were taken using purposive sampling technique and methods of data collection using questionnaires. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that the Tangible variable (physical evidence) significantly influences the variable customer satisfaction. While the Reliability, Responsiveness, Assurance, and Empathy variables do not significantly influence the customer satisfaction variable.